PELATIHAN PERMAINAN TRADISIONAL GOBAGSODOR DENGAN MENGINTEGRASIKAN NILAI-NILAI SOSIAL BUDAYA BAGI SISWA KELAS 5 SD KADUPAYUNG - Siti Nurazizah; Desty Endrawati Subroto; M. Hikmal Soulisa; Muhammad Haidir Ardhi; Muhamad Fajri; Erpin Erpin (CV. Denasya Smart Publisher, 2025)
The rapid development of the times has brought significant changes that should be preserved as heritage rather than ignored. Traditional games, rich in cultural and ethnic values and beneficial for children's development, are increasingly being replaced by modern games considered more realistic and personal. However, modern games should still pay attention to children's motor and cognitive aspects. This study utilizes Herbert Spencer's cultural theory, which states that society and culture evolve from simpler forms to more complex ones. Additionally, Jean Piaget's theory of child motor development is used, which argues that games significantly enhance children's cognitive abilities. This research aims to examine how traditional games influence children's development in the modern era. A qualitative method is employed to understand how children adapt traditional games into more modern forms to support their motor and cognitive development. The results show that traditional games can significantly contribute to developing children's abilities and character. The role of parents and teachers is crucial in preserving these traditional games, which are rich in meaning and cultural values. The study concludes that traditional games like gobag sodor contain cultural values embedded within their activities. Furthermore, these games include physical components such as agility, speed, coordination, strength, and balance, which are relevant in educational settings, both in schools and higher education institutions.